(untitled) (Research, Society and Development, 2025)
Prolonged caloric restriction, despite being frequently adopted as a strategy for weight loss and longevity, can trigger a series of physiological, hormonal, and behavioral changes, especially in women. This study aimed to investigate the impacts of this practice on neuroendocrine axes, reproductive function, and female psychological aspects. This is a narrative literature review based on national and international publications from recent years. The findings show that energy restriction compromises hormonal homeostasis, reduces basal metabolic rate, negatively affects the menstrual cycle, and may influence emotional well-being. Alterations in leptin, ghrelin, cortisol, and sex hormones were associated with loss of lean mass, menstrual dysfunctions, and disordered eating behavior. Additionally, psychological consequences such as irritability, anxiety, and cognitive distortions related to body image were observed. The gathered data reinforce the importance of individualized nutritional approaches and multidisciplinary follow-up to prevent adverse effects of caloric restriction in women. It is concluded that, although beneficial in some contexts, this practice requires caution, especially when conducted without proper professional guidance.